Heterogeneity of Genetic Admixture Determines SLE Susceptibility in Mexican - Hernández-Doño, Susana; Jakez-Ocampo, Juan; Márquez-García, José Eduardo; Ruiz, Daniela; Acuña-Alonzo, Víctor; Lima, Guadalupe; Llorente, Luis; Tovar-Méndez, Víctor Hugo; García-Silva, Rafael; Granados, Julio; Zúñiga, Joaquín; Vargas-Alarcón, Gilberto (Frontiers in Genetics, 2021)
Systemic Lupus Erythematosus (SLE) is an autoimmune inflammatory disorder for which Major Histocompatibility Complex (MHC) genes are well identified as risk factors. SLE patients present different clinical phenotypes, which are partly explained by admixture patterns variation among Mexicans. Population genetic has insight into the high genetic variability of Mexicans, mainly described through HLA gene studies with anthropological and biomedical importance. A prospective, case-control study was performed. In this study, we recruited 146 SLE patients. 234 healthy individuals were included as a control group; both groups were admixed Mexicans from Mexico City. The HLA typing methods were based on Next Generation Sequencing and Sequence-Based Typing (SBT). The data analysis was performed with population genetic programs and statistical packages. The admixture estimations based on HLA-B and -DRB1 revealed that SLE patients have a higher European ancestry proportion (48±8%) than healthy individuals (30±7%). In contrast, Mexican Native American components are diminished in SLE patients (44±1%) and augmented in Healthy individuals (63±4%). HLA alleles and haplotypes' frequency analysis found variants previously described in SLE patients from Mexico City. Moreover, a conserved extended haplotype that confers risk to develop SLE was found, the HLA-A*29:02~C*16:01~B*44:03~DRB1*07:01~DQB1*02:02, pC=0.02, OR=1.41. Consistent with the admixture estimations, the origin of all risk alleles and haplotypes found in this study are European, while the protection alleles are Mexican Native American. The analysis of genetic distances supported that the SLE patient group is closer to the European parental populace and farthest from Mexican Native Americans than healthy individuals. Heterogeneity of genetic admixture determines SLE susceptibility and protection in Mexican. HLA sequencing is helpful to determine susceptibility alleles and haplotypes restricted to some populations.